Analysis of the state of geometrization development and digital modeling in open-pit mining enterprises - M.S. Kunytska; D.S. Polishchyk; O.V. Shapochnikov (Технічна інженерія, 2025)
The article is devoted to the study of modern technologies of geometrization and digital modeling at open-pit mining enterprises. The relevance of the work is due to the requirements for optimizing mining processes, ensuring labor safety and increasing economic efficiency in the exploitation of deposits. The research methodology was a system analysis, statistical data processing and the study of scientific sources on the digitalization of the mining industry. Based on the analysis of literature and practical experience, it was established that the most common technologies are 3D modeling (25 %) and geographic information systems (20 %), which are supplemented by automated design systems (15 %), unmanned systems (15 %), artificial intelligence (15 %) and digital twins (10 %). It was determined that their integrated application provides an increase in the accuracy of reserve assessment by 15–20 % and a reduction in operating costs by 10–15 %. Key development trends are identified: integration of digital technologies, improvement of methods of collecting and processing geospatial data, introduction of machine learning algorithms for risk prediction. It is proven that modern geometrization methods contribute to the sustainable development of the industry by increasing the efficiency of resource use, reducing the cost of production and minimizing the impact on the environment.